5G Vehicular Network for Smart Vehicles in Smart City: A Review - U. Mustakim, Hamzah (Telkom University, 2020)
Smart vehicles is one of the innovation that can be used to increase the effectiveness of traffic in smart city as urban area and in the highway. In its development, smart vehicles not only require mobile communication services to ensure safety but also multimedia services for the passengers. These services must be integrated on intelligent transportation system. 5G vehicular network technology provides data communication services for intelligent transportation system via macrocells and smallcells to support smart vehicles which can drive at a maximum speed of 500Km/hour with multimedia services for passengers with data rates reaching the Gbps level. This paper will review 5G network architecture and emerging technologies that enabling vehicular network for smart vehicles in smart city.